Civil Law in the Context of Inheritance: Drafting a Validand Functioning Will - Arianti, Fitri (PT. Anagata Sembagi Education, 2024)
This research aims to explore the aspects of civil law related to inheritance with a focus on the preparation of legal and functional wills in Indonesia. Wills are important documents in estate planning that can reduce potential disputes between heirs. However, public understanding of the importance of wills and the legal provisions that govern them is still low. Through a normative juridical approach, this study collects data from literature studies, analysis of laws and regulations, case studies, and interviews with legal practitioners and the public. The results of the study show that the involvement of notaries in the preparation of wills is very important to ensure the validity of documents and prevent disputes. Although there are various educational programs regarding wills, their effectiveness still needs to be improved. The recommendations resulting from this study include the need for increased cooperation between legal practitioners, educational institutions, and community organizations in educating the public on the importance of heritage planning. Thus, it is hoped that public awareness of the preparation of wills will increase, so that the practice of inheritance planning in Indonesia can be more effective and in accordance with the applicable legal provisions.